2017
DOI: 10.1016/j.pss.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

The dynamical evolution and the force model for asteroid (196256) 2003 EH1

Abstract: This paper is devoted to the dynamics of asteroid (196256) 2003 EH1 that belongs to the Amor group. It is known that the asteroid 2003 EH1 is associated with one of the main annual meteor showersthe Quadrantids. In this work we analyze the influence of various perturbing factors on the asteroid motion. The perturbation's estimation was done by five different methods based on the nominal orbit evolution and the size of the initial confidence region. The most significant influences on the dynamical evolution of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…The orbital evolution of the asteroid (196256) 2003 EH1 has been studied by many authors, most recently by Kaˇnuchová and Neslušan (2007), Kholshevnikov et al (2016), Galushina et al (2017). Numerical integration of motion equations of the asteroid 2003EH1 and its 500 clones (Williams et al, 2004b;Galushina et al, 2017) showed that the orbits of the clones due to multiple close encounters with the planets, move away from the nominal orbit very quickly, which confirms the above. Consequently, in case of Quadrantid, any initial structure will be lost very quickly.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…The orbital evolution of the asteroid (196256) 2003 EH1 has been studied by many authors, most recently by Kaˇnuchová and Neslušan (2007), Kholshevnikov et al (2016), Galushina et al (2017). Numerical integration of motion equations of the asteroid 2003EH1 and its 500 clones (Williams et al, 2004b;Galushina et al, 2017) showed that the orbits of the clones due to multiple close encounters with the planets, move away from the nominal orbit very quickly, which confirms the above. Consequently, in case of Quadrantid, any initial structure will be lost very quickly.…”
Section: Introductionmentioning
confidence: 53%
“…In this paper, we have presented one of the possible scenarios for the dynamical evolution of the meteoroid stream formed by the asteroid (196256) 2003 EH1. Our analysis of the dynamics of meteoroid particles assumed to be released from the near-Earth asteroid (196256) 2003 EH1 revealed the complicated dynamical structure of its meteoroid stream, which approaches Jupiter's and Earth's orbits. Meteoroids inherit the dynamic properties of the asteroid but not all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Методика выявления вековых резонансов подробно описана в работах [12,13]. Рассмотрим здесь основные понятия.…”
Section: орбитальный резонансunclassified
“…∼ 1 au). ( 3552) Don Quixote, for example, has displayed recurrent activity from 1.23-2.72 au (Mommert et al 2014;Mommert et al 2020);(196256) 2003 EH 1 , associated with the Quadrantid meteor shower, might have been active when its perihelion distance was ∼ 1 au (Jenniskens 2004;Abedin et al 2015;Galushina & Sambarov 2017). If Phaethon exhibits activity at 0.14 au, it will point to a mechanism different than the one that drives its near-perihelion activity.…”
mentioning
confidence: 99%